Transportation of hydrogen for energy transition : financial analysis and strategic implications for the industry - Huerta, Felipe; Hönig, Vladimír, 1982-; Procházka, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the cost dynamics of hydrogen logistics, focusing on intermediary stages such as storage, transportation, and carrier conversion and reconversion. The study evaluates four transportation pathways: compressed hydrogen via repurposed pipelines, and liquefied hydrogen, ammonia, and methanol transported by truck. The primary goal is to identify the most cost-effective logistical solutions based on varying transportation distances and hydrogen throughput, while also considering key technical, economic, and technological readiness factors. Each stage is analyzed by evaluating required equipment, pathway processes, energy demand, and carrier losses, with a fixed hydrogen volume and transportation distance applied across all pathways. Cost evaluation includes capital expenditure (CAPEX), fixed costs, variable costs, and energy consumption, which are annualized to provide a consistent assessment. The total annual cost is derived by summing operational and investment expenses, resulting in specific product costs expressed in euros per kilogram of hydrogen (EUR/kg H₂). Repurposing pipelines emerges as the most cost-effective option at 1.86 EUR/kg H₂, significantly outperforming truck-based alternatives. While pipeline transportation offers both cost efficiency and enhanced safety, its large-scale deployment requires further technical validation and regulatory support. In circumstances where pipeline repurposing is impractical, truck-based hydrogen carriers represent a necessary alternative, each presenting distinct cost and technical challenges. Methanol offers an efficient and relatively cost-competitive transport option but is constrined by the limited industrial deployment of essential infrastructure, such as transport trailers. Liquid hydrogen, while capable of transporting large volumes, remains costly due to energy-intensive liquefaction, despite benefiting from low reconversion costs and moderate technological maturity.
Ammonia, benefiting from an established commercial market and favorable handling properties, faces economic constraints due to its high reconversion costs and associated toxicity risks. Pipeline repurposing continues to maintain its cost advantage across varying distances and input hydrogen flow rates, reinforcing its central role in Europe’s future hydrogen infrastructure. Across all transportation pathways, capital expenditures related to storage, conversion, reconversion, and infrastructure remain the primary cost drivers, underscoring the critical importance of achieving economies of scale. To ensure a secure and scalable supply, the European Union must advance regulatory frameworks, incentivize the development of large-scale projects, and strengthen strategic partnerships with potential supplier countries. Ultimately, the establishment of a diversified, robust, and well-regulated hydrogen logistics network will be essential for supporting Europe’s ambition to lead the global hydrogen economy.
Vedoucí práce: Vladimír Hönig
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses